2005
DOI: 10.1021/la047115r
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Study for Supermolecular Microstructures in Side-Chain Liquid Crystalline Polymer Films

Abstract: Atomic force microscopy (AFM) is employed to study the supermolecular microstructures of disclinations and inversion walls in thin films of a smectic side-chain liquid crystalline polymer. Two-dimensional nanostripes are formed in thin films when the material enters the smectic phase. A possible mechanism for their formation is also suggested. The stripes run parallel to the local director and thus decorate the overall patterns of nematic director around the disclinations and inversion walls. Three patterns in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This is expected since the precise nature of defects observed in the planar films will depend on the detailed balancing of distortion of defects in the bulk elastic energy, and surface anchoring energy. , For a thin film, the surface anchoring energy due to confined environments, and the strong interaction between LC molecules and substrate, dominates over the bulk elastic energy. In our previous work, we employed TEM and AFM to prove that the center of the integer disclination is lower than the surrounding material and the mesogenic groups are tilting out of the film plane. In such a geometric confined environment, the integer disclinations may be stabilized by “escaping core”, as shown in Figure a. Increasing the film thickness makes the bulk elastic energy become dominant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is expected since the precise nature of defects observed in the planar films will depend on the detailed balancing of distortion of defects in the bulk elastic energy, and surface anchoring energy. , For a thin film, the surface anchoring energy due to confined environments, and the strong interaction between LC molecules and substrate, dominates over the bulk elastic energy. In our previous work, we employed TEM and AFM to prove that the center of the integer disclination is lower than the surrounding material and the mesogenic groups are tilting out of the film plane. In such a geometric confined environment, the integer disclinations may be stabilized by “escaping core”, as shown in Figure a. Increasing the film thickness makes the bulk elastic energy become dominant.…”
Section: Resultsmentioning
confidence: 99%
“…The orientational properties are carried by the short mesogenic side chains, and the nature of the order parameter is then similar to the small molecule LCs . There are many theoretical and experimental indications that the values of elastic constants in side-chain liquid crystalline polymers are close to those in analogous small molecule LCs. , Recently, we reported the observation of two-dimensional stripes in thin films of a side-chain polymer using transmission electron microscopy (TEM) and atomic force microscopy (AFM). When the samples were cooled to the smectic phase, after a holding period in the nematic phase, a characteristic pattern of stripes developed. The orientation of stripes, along the local director, was demonstrated by correlating the direction of the stripes with electron diffraction patterns.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The condensate of epoxy liquid crystal has excellent mechanical, thermal, electrical, optical and other aspects of performance. 34,35 Zhang et al 36 and Han et al 37 reported the combination of carbon nanotubes (CNTs) and thermotropic liquid crystals (TLCs), it not only provides a useful way to align CNTs, but also dramatically enhances the TLC performance especially in the liquid crystal display technology. Biswas et al 38 and Zhao et al 39 reported the nanocomposite was prepared with exfoliated graphene nanoplatelets (GnP) and liquid crystalline polymer to achieve both high mechanical modulus and electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported that curing of LCE was accelerated by alignment of LCE on CF and anisotropic orientation of LCE enhanced dynamic modulus of CF‐reinforced LCE composites. Zhang et al and Han et al provided a useful method to align CNTs in thermosetting liquid crystalline (LC) polymer to enhance the liquid crystal display technology.…”
Section: Introductionmentioning
confidence: 99%